Microscopic findings of lung tissue and respiratory muscles in Chronic Obstructive Pulmonary Disease (COPD): Hallazgos microscópicos del tejido pulmonar y los músculos respiratorios en la Enfermedad Pulmonar Obstructiva Crónica (EPOC) - de Oliveira, Tales Lyra (2019)
Introduction: In chronic obstructive pulmonary disease (COPD), the diaphragm and sternocleidomastoid respiratory muscles (ECOM) work against increased mechanical loads due to limited air flow and changes in chest conformation due to the condition of pulmonary hyperinflation. Objective: To evaluate the histopathological changes present in the lungs and respiratory muscles (diaphragm and ECOM) of the corpses affected by COPD. Materials and methods: This is a blind and descriptive study with analysis of histological images of biopsy. The history of smoking associated with the presence of pulmonary anthracosis, septal thickening and emphysematous bullae included the inclusion criteria of the study. The study was conducted by optical microscopic analysis of histological sheets obtained from 36 corpses with COPD. The histopathological diagnosis was made by a pathologist who did not know the objectives of the study. Results: In the diaphragm, there was the presence of interposed adipose tissue, muscle atrophy, removal of muscle fibers and fibrosis. In ECOM, the elimination of muscle fibers, muscular atrophy, interposed adipose tissue, muscle hypertrophy and thickening of the tendons were also evident. Conclusions: The changes found in the diaphragm and ECOM muscle biopsies of the bodies with COPD were evidenced as a mechanism of compensation and / or dysfunction of the respiratory system due to biomechanical alterations promoted by the disease.